Learning Trajectory on Probability Using the Context of the Bekulo Tradition - Mandasari, Novianti; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely; Mulyono, Budi (Mimbar Sekolah Dasar, 2025)
In everyday life, individuals are required to be cautious in making decisions and analyzing the possibilities of various alternatives. Probability theory emerges as one of the important branches of mathematics that provides an understanding of uncertainty and ways to measure the likelihood of an event. However, field observations reveal that many students still encounter difficulties in understanding probability, particularly in the subtopic of combinations. These difficulties are generally caused by abstract learning processes, limited contextual activities, and the lack of connection between mathematics and real-life experiences or local culture close to students’ lives. This study aims to design probability learning based on Indonesian Realistic Mathematics Education (IRME) by utilizing the Bekulo tradition in Rejang Lebong Regency as a relevant local cultural context. The method employed is design research with a validation study type, involving ninth-grade students of SMP IT Salsabillah Rejang Lebong as research subjects. Data were collected through observation, documentation, and interviews. In this study, the researchers developed a Hypothetical Learning Trajectory (HLT) adapted to the Bekulo tradition context. The results show that integrating IRME with cultural contexts can effectively support the development of students’ understanding of the concept of combinations in a more meaningful way. These findings affirm that culturally rooted learning designs not only enrich students’ learning experiences but also foster their appreciation of local wisdom while making mathematics more relevant to everyday life.